The architectural evolution of Innes House, Moray - McKean, Charles (Proceedings of the Society of Antiquaries of Scotland, 2004)
Documentary evidence appears to date the construction of Innes House, near Elgin, to c 1640, whereas a drawing of c 1590 implies there was a castle on the site some 50 years earlier. This paper seeks to resolve that paradox by dissecting Innes through documents and drawings, correlated with a minute study of its fabric through a sequential examination of its principal structural components; and, by doing so, evaluating the extent that information gleaned from a building’s fabric can supplement, support or deny documentary history.